Pengembangan Back-End Sistem Informasi Pendataan Sekolah Di Pendar Foundation - Sofyan Mufti Prasetiyo; Rifsi Baehaki; Suharjono; Maulidya Nur Ananda P. (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The purpose of developing a data collection information system for the Pendar Foundation Community is to facilitate the recording and grouping of data on "Village School" activities for the Pendar Foundation Community The Pendar Foundation Community is a social organization engaged in philanthropy and education aimed at the children of farmers and laborers in rural areas of Yogyakarta . Pendar Foundation wants rural children to get sufficient knowledge and there is no gap in knowledge between villages and cities, so they hold "Village School" activities. “Village Schools” are held in several villages with a large number of children and with a variety of materials, but the activity data recording method currently used is still manual, namely using Microsoft Word. The Pendar Foundation community feels that this method is not effective because they often find it difficult to synchronize data. For this reason, the Pendar Foundation Community needs an information system that can record every "Village School" activity. In addition, the system is also designed to be accessible to all community members so that all members can view and manage data in detail. Information system development is carried out using the CodeIgniter framework with a MySQL database. The results of this research are database implementation and system logic